The development of an inexpensive passive marker system for the analysis of starts and turns in swimming - Slawson, S. E.; Conway, P. P.; Justham, L. M.; West, A. A. (Procedia Engineering, 2010)
This paper details the research and development of an automated vision system that enables biomechanical analysis of swimming skills, i.e. the start and turns, without the need for traditional manual digitisation techniques. Small, non encumbering swimmer worn markers were developed using an array of Light Emitting Diodes (LED's). These markers were used to create a distinguishable feature that could be tracked throughout a video sequence. It was important that the markers worked in both under and over water environments to facilitate the analysis of both starts and turns.